Multimodal inquiry learning framework in meaning-making of the concept of force. - Shahari, Shariza (Human Resource Management Academic Research Society (HRMARS), 2023)
Past studies have shown that the interactions that appear between existing knowledge and new knowledge of students will result in a conceptual change in students. However, the process of conceptual change is complex and requires careful planning by teachers. In this concept paper, the constructed Multimodal Inquiry Learning (MIL) framework introduced the physics topic of force studied by matriculation students in the first semester of their studies. Learning that involves verbal and non-verbal communication is a common feature of multimodal learning. While inquiry learning uses various modes of communication including verbal, visual, pictorial, graphic, and text is called multimodal inquiry learning. Past studies have proven that multimodal representation is found to play a role in the conceptual change for the concept of heat, but how the conceptual change takes place in the student's mind through meaning-making has yet to be explained by them. The MIL framework suggested by this study is expected to help physics teachers/lecturers, especially in improving their pedagogical practices.